Prospects of tobacco sector due to changing of union subsidy system - Bittner, Beáta (Acta Agraria Debreceniensis, 2008)
Some 80% of the revenues from tobacco production originate from subsidies, therefore the existence of the tobacco industry basically depends on the system of subsidies. According to the current position, in the transitional period of introduction of the CAP reform (from 2006 to 2009) at least 40% of tobacco premiums shall be decoupled from the production, while the tobacco producing member states may decide to continue to pay the remaining 60% (or a less rate, depending on the rate of decoupling) in a coupled form. Tobacco premiums shall be fully decoupled as from the 2010 crop, however farmers will be eligible only for 50% of the subsidies, and the rest 50% shall be used for subsidising rural developments in tobacco producing regions (Radóczné, 2007). This change affects the section very seriously. In EU-15 member states this system was introduced in 2006, which resulted in giving up tobacco growing by high percentage of the farmers (70-80% reduction of tobacco production in Greece and Belgium, and 45% reduction in Portugal). In Hungary – due to the small scale of the tobacco section – this rate reduction in production would jeopardise the existence of the section, therefore we are interested in maintaining the existing system of coupled subsidies to as a large extent and for as long time as possible. This study shows the possibility of tobacco sector before and after introducing the changes in the system of subsidies, and formulates the most serious problems and roles of the sector.